Creative Economy as a Driver of Sustainable Tourism in the Slopes of Mount Merbabu - Ahmad Indarto, Bambang; Rachmawati, Meida (International Journal of Law Social Sciences and Management, 2025)
This study examines the role of the creative economy as a driving force for sustainable tourism in the Merbabu Mountain slope area. Using a qualitative descriptive approach, the research was conducted over six months, involving 25 key informants including community leaders, creative economy entrepreneurs, tourism managers, village officials, and tourists. The results show that the Merbabu Mountain slope area possesses diverse creative economy potential, particularly in traditional culinary arts and local resource-based handicrafts. The integration of creative economy with tourism has successfully increased tourist length of stay from 1 to 2.5 days and increased creative economy actors' income by 40% within a year. Despite challenges in product standardization and digital market access, an integrated development model was created comprising human resource capacity building, local wisdom-based product development, tourism package integration, and digital marketing development. The research recommends establishing a creative economy management unit at the regional level to ensure program sustainability. This study contributes to both theoretical understanding and practical implementation of creative economy integration in sustainable mountain tourism development, providing a replicable model for similar regions across Indonesia.